2003
DOI: 10.1172/jci200318945
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotection by the farnesoid X receptor agonist GW4064 in rat models of intra- and extrahepatic cholestasis

Abstract: Farnesoid X receptor (FXR) is a bile acid-activated transcription factor that is a member of the nuclear hormone receptor superfamily. Fxr-null mice exhibit a phenotype similar to Byler disease, an inherited cholestatic liver disorder. In the liver, activation of FXR induces transcription of transporter genes involved in promoting bile acid clearance and represses genes involved in bile acid biosynthesis. We investigated whether the synthetic FXR agonist GW4064 could protect against cholestatic liver damage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 46 publications
4
80
1
Order By: Relevance
“…(29) Several drugs that target these receptors are known to upregulate ABCB4 in the animal. (30)(31)(32)(33) It has also been shown that statins enhance ABCB4 expression in the rat. (34,35) Recently, clinical trials have shown that targeting nuclear receptors with the farnesoid X receptor agonist obeticholic acid (36) or with the peroxisome proliferator-activator receptor-a agonist bezafibrate (37) was promising in the treatment of chronic liver diseases with poor response to ursodeoxycholic acid.…”
Section: Discussionmentioning
confidence: 99%
“…(29) Several drugs that target these receptors are known to upregulate ABCB4 in the animal. (30)(31)(32)(33) It has also been shown that statins enhance ABCB4 expression in the rat. (34,35) Recently, clinical trials have shown that targeting nuclear receptors with the farnesoid X receptor agonist obeticholic acid (36) or with the peroxisome proliferator-activator receptor-a agonist bezafibrate (37) was promising in the treatment of chronic liver diseases with poor response to ursodeoxycholic acid.…”
Section: Discussionmentioning
confidence: 99%
“…All of the major steps in the enterohepatic circulation of bile acids are regulated by FXR (32,33). The FXR ligand GW4064 has been reported to attenuate cholestatic injury in rat models of cholestasis (34). Furthermore, UDCA, which is the current standard therapy for PBC, is a relatively stronger pregnane X receptor agonist and a weaker FXR agonist.…”
Section: Discussionmentioning
confidence: 99%
“…10,15,56 Lipid emulsions based purely on vegetable oils also contain higher concentrations of phytosterols such as stigmasterol, β-sitosterol, and campesterol, compared with other lipid sources (eg, those containing fish oil). 57 There is evidence that phytosterols may contribute to the development of IFALD, [58][59][60][61][62][63][64][65][66][67][68] though the role of phytosterols in the development of IFALD remains controversial. Phytosterols have been observed to accumulate in the liver and plasma in children receiving a soybean oil emulsion, 58 elevated serum phytosterol concentrations have been shown to correlate with the development of cholestatic liver disease in infants and children requiring long-term PN, 64,65,67 and liver concentrations of phytosterols have been shown to correlate with liver fibrosis in PN-dependent children with IF.…”
Section: Intravenous Lipid Supply and Cholestatic Liver Diseasementioning
confidence: 99%
“…Animal studies have suggested that phytosterols inhibit transcription of bile transport proteins via antagonism of the farnesoid X receptor. [59][60][61][62][63]66,69 The addition of stigmasterol to a fish-oil emulsion resulted in activation of hepatic macrophages in mice, suggesting that phytosterols might act synergistically with lipopolysaccharides and other mediators to promote inflammation and hepatocellular injury. 66 The rate of lipid infusion can also contribute to liver injury.…”
Section: Intravenous Lipid Supply and Cholestatic Liver Diseasementioning
confidence: 99%